Parents’ decisions of children vaccination in three public clinics at Yan, Kedah / Mohamad Syafiqir Rahman Mohamad Nazir and Johan Mukhlis Jan Zakri - Mohamad Nazir, Mohamad Syafiqir Rahman; Jan Zakri, Johan Mukhlis (2019)
Lower level of decisions among parents towards children vaccination is brought along with numerous catalysts which are the misinformation, parents’ attitudes and parents’ knowledge about the importance of vaccine on children. Moreover, religiosity and holistic postmodern spirituality were also suggested as obstacles to childhood immunization as stated by Ruijs, et al., (2012). One of the factors that catalyse the growth of low level of decisions among parents in children vaccination is misinformation. According to Yu, et al., (2016), incorrect information and lack of understanding about the benefits of vaccine has weighed multiple factors in decision on Human Papillomavirus (HPV) vaccines. Variety sources of information also play vital roles in disseminating incorrect information towards the audience, especially among parents themselves (Al-Zahrani, 2013). According to Danova, Salek, Kocourkova, & Celko (2015), the wide spreading of false statements about vaccination on web pages led the incremental of hesitancy and refusing parents to vaccinate their children in which the web pages are heated up by the groups of people who refuse to vaccine their children in principle.